2006
DOI: 10.1017/s0012162206000570
|View full text |Cite
|
Sign up to set email alerts
|

Standardized assessment of behavior and adaptive living skills in juvenile neuronal ceroid lipofuscinosis

Abstract: We obtained information about the behavioral, psychiatric, and functional status of 26 children (13 males, 13 females) with juvenile neuronal ceroid lipofuscinosis (JNCL; mean age 12y 3mo [SD 3y 4mo]; range 6y 9mo to 18y 8mo). Twenty-five children had visual impairment and 18 were known to have a positive seizure history before enrollment. Parents completed the Child Behavior Checklist, Scales of Independent BehaviorRevised, and a structured interview to assess obsessivecompulsive symptoms. Participants exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…Our initial studies 18-20 confirmed high rates of behavioral problems in children with juvenile neuronal ceroid lipofuscinosis. These symptoms, along with cognitive impairments, appear to precede onset of motor impairment, 3 and do not appear to be influenced by genotype.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Our initial studies 18-20 confirmed high rates of behavioral problems in children with juvenile neuronal ceroid lipofuscinosis. These symptoms, along with cognitive impairments, appear to precede onset of motor impairment, 3 and do not appear to be influenced by genotype.…”
Section: Resultssupporting
confidence: 64%
“…21 Bäckman and colleagues 6 reported sex differences in behavioral symptoms among a Finnish cohort of children with juvenile neuronal ceroid lipofuscinosis: females exhibited greater anxiety (per parent report) and greater social difficulties (per teacher report) in comparison with males, although these findings were not replicated in our North American sample. 20 We also have hypothesized that behavioral and mood symptoms would follow an inverse U-shaped function in which problems initially worsen as disease advances, before dropping off in the later stages of the illness, as motor impairment limits the behavioral repertoire. Figure 2, Panels A-C illustrate this pattern for several behavioral domains, with scatterplots containing all observations at each time point for each child who has undergone parental ratings of behavior with the Child Behavior Checklist, representing 369 total evaluations of 70 children since 2003.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Neuropsychological examinations have added to our understanding. 4, 5 Integrating these clinical findings with those from the mouse models for JNCL will be crucial in determining the precise pathophysiology.…”
Section: Pathogenesismentioning
confidence: 99%
“…34 In our own investigations, we have used remote telephone assessment to evaluate adaptive function in juvenile Batten disease. 35 In clinical trials of psychosocial interventions, remote technology is also now being utilized to deliver behavior therapy. Finally, using one or a small number of centralized, expert raters to conduct assessments remotely for multiple clinical research sites, it may be possible to minimize intra-examiner bias and inter-examiner variability, ultimately reducing error variance and improving data quality.…”
Section: Discussionmentioning
confidence: 99%